Analysis of Teachers' Understanding of Natural Material Media in Learning at Early Childhood Education in Tapaktuan District - Rita Yulia; Didi Yudha Pranata; Zahraini Zahraini (Journal of Educational Sciences, 2026)
Early Childhood Education plays an important role in supporting children’s cognitive, social, emotional, and creative development through meaningful learning experiences. Learning activities at this level require appropriate media that can stimulate children’s curiosity and active participation. Natural material media, which utilize objects from the surrounding environment such as leaves, stones, seeds, sand, and shells, offer opportunities for experiential learning that are concrete and contextually relevant to children’s daily lives. Limited understanding among teachers regarding the use of natural material media may reduce the effectiveness of such learning resources in classroom practice. This study aims to analyze teachers’ understanding of natural material media in learning activities in Early Childhood Education institutions in Tapaktuan District. A qualitative descriptive approach was employed to explore teachers’ knowledge, planning ability, and implementation of natural material media in classroom learning. Data were collected through interviews, observations, and documentation involving teachers from several Early Childhood Education institutions. Results indicate that teachers generally recognize the potential of natural materials as learning media and have applied them in simple learning activities that encourage creativity and exploration. Greater pedagogical planning and professional support would further enhance the effective use of natural material media in Early Childhood Education learning environments.